Análise exergética dos processos de expansão de vapor em uma usina de açúcar e etanol - Schiaveto, Gabriel Sanchez (Universidade Federal de São Carlos, 2025)
Steam is the main source of energy in the sugar-ethanol industry, being used to generate mechanical work in the mills, juice heating and evaporation, vacuum generation, ethanol distillation, zeolite regeneration, yeast drying and electricity generation. Each of these processes requires steam under different temperature and pressure conditions, therefore, steam throttling is inevitable. There are two main ways to reduce steam pressure and temperature: backpressure turbines and steam conditioning valves. This study aims to quantify the losses of availability and the exergetic efficiencies associated with turbines and steam conditioning valves in a sugar and ethanol mill located in the São Paulo Estate. To minimize exergy destruction, the actual operating condition (1) was calculated and compared with three simulated and improved scenarios: enabling the intermediate extractions of the turbines (2), installing a new high-pressure turbogenerator (3), and combining both modifications (4). Of the 533.35 MW available for performing work in the studied plant, 492.39 MW are effectively utilized, with the remaining 40.96 MW representing the loss of availability. The exergetic efficiency calculated for the current condition is 92.32%. The simulated scenarios presented gains of 7,223 kW, 15,844 kW and 18,346 kW of useful work compared to the present configuration, corresponding to increases of 1.19 p.p., 2.88 p.p. and 3.39 p.p. in system exergetic efficiency, reaching 95.71% for the best simulated scenario.
Exergy analysis of steam expansion processes in a sugar and ethanol plant
Keywords: Exergia; Cogeração; Expansão de vapor; Exergy; Cogeneration; Steam expansion; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; 9. Indústria, Inovação e Infraestrutura